Roar of the thunder dragon - West, Tracey, 1965- (West, Tracey, 1965- Dragon Masters, 2017)
Lalo the baby lightning dragon has been taken by Eko, a rogue Dragon Master, who ran away with her thunder dragon years before--now she is back looking to make allies of the other dragon masters, and so gain control over all of the dragons in Griffith.